Answer:
first you take the square root or 0.9, 2.7, 1.7, and 0.4 which will equal=
0.9= ~0.94
2.7=~1.64
1.7=~1.30
0.4=~0.63
0.94 - 1.64 + 1.30 + 0.63 = 1.23
hope this helps! C:
Answer:
Option B
Option C
Option D
All of these are correct
Step-by-step explanation:
Option B is correct because:
2x + 1 + 2x + 3 = 4x + 4
=> 4x + 4 = 4x + 4
Option C is correct because:
x + 3x + 4 = 4x + 4
=> 4x + 4 = 4x + 4
Option D is correct because:
2(2x + 2) = 4x + 4
=> 4x + 4 = 4x + 4
Option A is incorrect because:
4(x + 4) = 4x + 4
=> 4x + 16 ≠ 4x + 4
Answer:
64
Step-by-step explanation:
S = p/(q +p -pq)
q +p -pq = p/s
q -pq = p/s - p
q(1-p) = p/s - p
q = (p/s - p) / (1-p)